O processo administrativo como instrumento democrático de participação - Taveira Junior, Rubens Silveira (2012)
The present work is a new reading of what the administrative process and its importance in relation to new forms of interpretation of Administrative Law, which is given to affirm the concept of legality and your reflexes in this branch of law, noting also their bias implementer of democracy. The study of this issue is limited to the federal administrative process that has as a general rule the Law 9.784/99, with subsidiary application in all the administrative competence of the Union Building on a historical analysis of democracy and what was characterized as participation democratic enough to conclude that such a policy institute was largely the story of a privileged class holding power, excluding political participation of various social classes. Liberalism also has used democracy to achieve their economic desiderata, it usurped the democratic ideals and instruments such as suffrage, to create a system of foundations that legitimize the preservation of private property and then serve as a tool to maintain power. It is understood that only a real democratic participation in a democracy is perfected taken by substantial, in particular the proposal by Paul Bonavides, considering how essential the participation of ordinary citizens in decision making, adding a new connotations to the word democracy to give it the characteristic of a fundamental right. It is essential to a real process characterization as a tool for participation, to become a reinterpretation of what is meant by process, understand it as a procedure described by contradiction we have the theory advocated by Elio Fazzalari. The contradiction is fundamental to such a task, then, from the exercise of this right, you can talk about the effectiveness of the principle of democratic participation. However, essential to the proposed application process as an instrument of participation, is an analysis of standards that make up the Law 9.784/99, since, by verifying the nature of such rules, one can envision an application from the normative weight informants principles of such a law, whereas values democracy and dignity that should permeate all decisions handed down by the Administration. Will be checked also two institutes democratic conveyed by Law 9.784/99, which are the public consultation and public hearing, these instruments are characterized by expanding the democratic bias of the administrative process, as well as legitimizing the conduct of the trustee to prolatar decision which has effects in a community. The proposed procedural purposes exceeds the primacy legalistic for many years was stressed in relation to that instrument, and the interpretation of the principles and the balancing of interests gained significant importance in Legal Dogmatics, especially when it sees a new way to operate the state. For such a task, it is necessary to analyze the current functions of the administrative process, particularly, to provide democratic legitimacy to citizens by fostering a real possibility of their participation in government decisions.